Personhood and companionship among Evenki and their reindeer in Eastern Siberia - Landerer, Evelyn (Universitetet i Tromsø, 2009)
This thesis aims to contribute to our understanding of human-reindeer relations among nomadic hunters and reindeer keepers and is based on a discussion of manifestations of personhood in Siberia. I then relate these to contemporary theories in human-animal relations and argue that in the case of this research setting, these relations exceed notions of symbiotic domestication and social contracts. I discuss this topic within the context of Evenki hunters and reindeer breeders living in Katangskiy Rayon, the northernmost district of Irkutskaya Oblast, Russia. I argue that lack of collectivization in this area together with the absence of the notion of reindeer as commodity aimed towards a centralized (Soviet times) or market economy has led to the development of interpersonal companionship in the forest based on respect for the individuality and intentionality of the reindeer.